Training Needs Assessment For Geologist Based On Grounded Theory - Ageng Watugilang; Jerry Heikal (Jurnal Ekonomi dan Bisnis Digital, 2024)
As an effort to increase capacity in the mining sector, especially to create qualified geologists to estimate mineral and coal resources, an active role is needed from all parties to provide good quality training for geologists. This research uses grounded theory. Five resource persons who are geologists with different levels of work experience, namely junior geologists, middle level geologists and senior geologists, conducted very in-depth interviews regarding the needs of geologists and mining training. . For the question what a factors for geologists in choosing a training vendor The research found 13 codings, then from these 13 codings there were several codings that were similar to each other, which we then grouped into axial coding which formed 7 categories, and from these 7 categories formed 4 themes because they were close (selective coding), and the high frequency is quality. For the question What training topics are needed by geologists the research found 11 coding , then from these 11 codings there were several codings that were similar to each other, which we then grouped into axial coding which formed 5 categories, and from these 5 categories formed 3 themes because they were close (selective coding),